Phosphorus and Compost Management Influence Maize (Zea mays) Productivity Under Semiarid Condition with and without Phosphate Solubilizing Bacteria - Amanullah,; Khan, Adil (Frontiers in Plant Science, 2015)
Phosphorus (P) unavailability and lack of organic matter in the soils under semiarid climates are the two major constraints for low crop productivity. Field trial was conducted to study the effects of P levels, compost application times and seed inoculation with phosphate solubilizing bacteria (PSB) on the yield and yield components of maize (Zea mays L., cv. Azam). The experiment was conducted at the Agronomy Research Farm of The University of Agriculture Peshawar-Pakistan during summer 2014. The experiment was laid out in randomized complete block design with split plot arrangement using three replications. The two PSB levels [(1) inoculated seed with PSB (+) and (2) seed not inoculated with PSB (- or control)] and three compost application times [(30, 15 and 0 days before sowing (DBS)] combination (six treatments) were used as main plot factor, while four P levels (25, 50, 75 and 100 kg P ha-1) used as subplot factor. The results confirmed that compost applied at sowing time and P applied at the two higher rates (75 and 100 kg P ha-1) had significantly increased yield and yield components of maize under semiarid condition. Maize seed inoculated with PSB (+) had tremendously increased yield and yield components of maize over PSB-control plots (-) under semiarid condition.